Program Pengembangan Interaksi Sosial Anak di TKIT Baitusshalihin: Children's Social Interaction Development Program at Baitusshalihin Kindergarten - Nadia Fadila; Heliati Fajriah; Muthmainnah (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
TKIT Baitusshalihin is one of the institutions that implements social interaction development programs through various activities, but there are still some children who are still alone during the learning process. This study aims to describe the form of social interaction development programs and the factors that hinder the children's social interaction development program at TKIT Baitusshalihin. Social interaction is an important aspect in early childhood development, because it is the basis for the formation of communication skills, cooperation, and building interpersonal relationships. The research method used is a descriptive qualitative method. The subjects in this study were children aged 5-6 years (grade B). Data collection techniques in this study were observation, interviews and documentation. Observations include programs that exist in the school, the study conducted interviews with class B5 teachers and the principal. In the documentation stage, the researcher took photos related to the social interaction development program. The results of the study indicate that the social interaction development program for children at TKIT Baitusshalihin is divided into two programs: an internal school program and an outing class program. The internal school program includes 10 centers (natural materials center, physical exercise, origami, worship, gardening, art, painting, numeracy, literacy, and design) and extracurricular activities. The outing class is a field trip activity.   ABSTRAK  TKIT Baitusshalihin merupakan salah satu lembaga yang melaksanakan program pengembangan interaksi sosial melalui berbagai kegiatan, tetapi masih ada sebagian anak yang masih menyendiri ketika proses pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan bentuk program pengembangan interaksi sosial dan faktor kendala program pengembangan interaksi sosial anak di TKIT Baitusshalihin. Interaksi sosial merupakan aspek penting dalam perkembangan anak usia dini, karena menjadi dasar bagi terbentuknya kemampuan berkomunikasi, bekerja sama, dan membangun hubungan interpersonal. Metode penelitian yang digunakan adalah metode kualitatif deskriptif. Subjek dalam penelitian ini adalah anak-anak usia 5-6 tahun (kelas B). Teknik pengumpulan data dalam penelitian ini observasi, wawancara dan dokumentasi. Observasi memuat program-program pengembangan interaksi sosial yang ada di sekolah, wawancara dilakukan dengan guru kelas B5 dan kepala sekolah. Pada tahap dokumentasi peneliti melakukan pengambilan foto yang berkaitan dengan program pengembangan interaksi sosial. Hasil penelitian menunjukkan bahwa program pengembangan interaksi sosial anak di TKIT Baitusshalihin dibagi menjadi dua program yaitu program internal sekolah dan program outing class yaitu  program internal sekolah meliputi 10 sentra (sentra bahan alam, olah tubuh, origami, ibadah, berkebun, seni, melukis, numerasi, literasi, rancang bangun) dan ekstrakurikuler. Adapun outing class yaitu kegiatan field trip.